2010
DOI: 10.3945/ajcn.2010.29383
|View full text |Cite
|
Sign up to set email alerts
|

Puberty and observed energy intake: boy, can they eat!

Abstract: The observed intake patterns are congruent with known sexual dimorphisms for body composition, peak growth velocity, and pubertal development. Consistent with their higher energy requirements, males can consume significantly larger amounts of food than females, especially during later puberty. This trial was registered at clinicaltrials.gov as NCT00320177.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 30 publications
1
55
0
1
Order By: Relevance
“…Plausible explanations for the higher SDC among male adolescents could be that teenage boys in general have higher food consumption than girls [40] and that boys favor foods of sweet taste more than similarly-aged girls [41]. In addition, it has been reported that teenage girls spend more of their money on items other than food, such as clothing and personal care, compared to boys [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Plausible explanations for the higher SDC among male adolescents could be that teenage boys in general have higher food consumption than girls [40] and that boys favor foods of sweet taste more than similarly-aged girls [41]. In addition, it has been reported that teenage girls spend more of their money on items other than food, such as clothing and personal care, compared to boys [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…However, all regression analyses were adjusted for bodyweight (zBMI), which according to Jakes et al [51] has considerable advantages over adjusting for total energy intake. A final limitation was that no measures of pubertal stage or menstrual cycle were taken into account as these could possible affect energy intake and SR [33,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…So what messages do these studies convey? The lack of effect of full nutritional supplementation could be explained by the fact that the subjects downregulated their own energy and food intake at other times during the day, so an energy homeostatic mechanism may be in operation during prepuberty, in contrast to the accelerated nutritional requirements in late puberty, especially in boys [14]. The effect of adding specific growth-associated micronutrients alone is impressive, and although it is not yet clear whether attention to this level of detail will improve GH responsiveness, the overall message from both studies is that we should perhaps pay more attention to nutritional factors in short children, especially when a growth retardation process is implicated.…”
Section: Methodsmentioning
confidence: 99%